EFFECT OF ANTIEPILEPTIC DRUGS ON ERYTHROCYTE OSMOTIC FRAGILITY AND LIPID-PEROXIDATION - YALÇIN, AHMET SUHA (ELSEVIER SCIENCE BV, 1994)
Epileptic children receiving antiepileptics were studied to investigate the effect of carbamazepine and phenobarbital therapy on erythrocyte osmotic fragility and lipid peroxidation. Significant differences between the two groups were observed in erythrocyte osmotic fragility. In addition, there was a significant increase in erythrocyte malondialdehyde release in the epileptic group compared to controls. It is suggested that the use of antioxidants in addition to antiepileptic drugs may be beneficial.
Keywords: CARBAMEZEPINE; ERYTHROCYTE LIPID PEROXIDATION; ERYTHROCYTE OSMOTIC FRAGILITY; PHENOBARBITAL; VITAMIN-E STATUS; EPILEPSY; THERAPY; CELLS; ACID